Innovation and identity in distance language learning and teaching - White, Cynthia (Multilingual Matters, 2007)
Innovation in distance language learning and teaching has largely focused on developments in technology and the increased opportunities they provide for negotiation and control of learning experiences, for participating in collaborative learning environments and the development of interactive competence in the target language. Much less attention has been paid to pedagogical innovation and still less to how congruence develops between particular pedagogical approaches, various technologies and the skills, practices, actions and identities of language learners and teachers. In this article I explore the process of innovation in distance language teaching from the point of view of key participants in the process, the teachers, and the ways in which their identities are disrupted and challenged as they enter new distance teaching environments. Innovative approaches to distance language teaching are analysed for the insights they provide into the sites of conflict and struggle experienced by teachers, experiences which have a major impact on their selves as distance teachers and on the course of innovation. To conclude I argue that attention to issues of identity can deepen our understanding of innovation, of the tensions that are played out in the experiences and responses of teachers, and of the ways they accept or resist the identity shifts required of them.
doi: 10.2167/illt45.0
Keywords: Distance education; Identity; Innovation; Language teaching; Fields of Research::420000 Language and Culture::420100 Language Studies